Akiva : life, legend, legacy - Hammer, Reuven (Lincoln : University of Nebraska Press ; Philadelphia : The Jewish Publication Society, 2015)
"The legendary Akiva ben Yosef has fascinated Jews for centuries. One of and arguably the most important of the Tannaim, or early Jewish sages, he lived during a crucial era in the development of Judaism as we know it today, and his theology played a major part in the development of Rabbinic Judaism. Reuven Hammer details Akiva's life as it led to a martyr's death and delves into the rich legacy Akiva left us.That legacy played an extraordinarily important role in helping the Jewish people survive difficult challenges and forge a vibrant religious life anew and it continues to influence Jewish law, ethics, and theology even today. Akiva's contribution to the development of Oral Torah cannot be overestimated, and in this first book written in English about the sage since 1936, Hammer reassesses Akiva's role from the period before the destruction of the Temple in 70 CE until the Bar Kokhba Revolt in 135 CE. He also assesses new findings about the growth of early Judaism, the reasons why Akiva was so outspoken about "Christian Jews," the influence of Hellenism, the Septuagint, and the canonization of the Hebrew Bible. Ultimately, Hammer shows that Judaism without Akiva would be a very different religion"--
"Reuven Hammer traces the life of the great and legendary Sage, from youth to a martyr's death, and his many contributions to Rabbinic Judaism"--
Akiva's early life -- Becoming a sage -- The new sage and public figure -- The mystical interpreter of Torah -- The organizer of Torah -- Akiva and the Song of Songs -- Aspects of Akiva's theology -- Akiva's resistance, imprisonment, and death -- The man and his legacy.
"Published by the University of Nebraska Press as a Jewish Publication Society book."
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Akiba ben Joseph, -- approximately 50-approximately 132.; Akiba ben Joseph, -- approximately 50-approximately 132.; Tannaim -- Biography; Jews -- History -- Bar Kokhba Rebellion, 132-135.; Martyrdom -- Judaism; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Judaism / History; BIOGRAPHY & AUTOBIOGRAPHY / General; RELIGION / Judaism / General; Jews; Martyrdom -- Judaism; Tannaim; 132-135; Electronic books; Biography; History